Hyaluronic Acid Present in the Tumor Microenvironment Can Negate the Pro-apototic Effect of a Recombinant Fragment of Human Surfactant Protein D on Breast Cancer Cells - Murugaiah, Valarmathy; Agostinis, Chiara; Varghese, Praveen M.; Belmonte, Beatrice; Vieni, Salvatore; Alaql, Fanan A.; Alrokayan, Salman H.; Khan, Haseeb A.; Kaur, Anuvinder; Roberts, Terry; Madan, Taruna; Bulla, Roberta; et al. (Frontiers in Immunology, 2020)
Human surfactant protein D (SP-D) belongs to the family of collectins that is composed of a characteristic amino-terminal collagenous region and a carboxy-terminal C-type lectin domain. Being present at the mucosal surfaces, SP-D acts as is a potent innate immune molecule and offers protection against non-self and altered self-such as pathogens, allergens, and tumour. Here, we examined the effect of a recombinant fragment of human SP-D (rfhSP-D) on a range of breast cancer lines. Breast cancer has four molecular subtypes characterised by varied expression of oestrogen (ER), progesterone (PR) and EGF receptors (HER2). The cell viability of HER2 over-expressing (SKBR3) and triple-positive (BT474) breast cancer cell lines (but not of triple-negative cell line (BT20), was reduced following rfhSP-D treatment at 24h. Upregulation of p21/p27 cell cycle inhibitors and p53 phosphorylation (Ser15) in rfhSP-D-treated BT474 and SKBR3 cell lines signified G2/M cell cycle arrest. Cleaved caspase 9 and 3 were detected in rfhSP-D- treated BT474 and SKBR3 cells, suggesting an involvement of intrinsic apoptosis pathway. However, rfhSP-D-induced apoptosis was nullified in the presence of hyaluronic acid whose increased level in breast tumor microenvironment is associated with malignant tumor progression and invasion. rfhSP-D bound to solid-phase HA and promoted tumor cell proliferation. rfhSP-D-treated SKBR3 cells in the presence of hyaluronic acid showed decreased transcriptional levels of p53 when compared to SKBR3 cells treated with rfhSP-D only. Thus, hyaluronic acid appears to negate the anti-tumorigenic properties of rfhSP-D against HER2-over-expressing and triple-positive breast cancer cells.